2020
DOI: 10.1016/j.ocarto.2020.100128
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 13 (IL-13)-regulated expression of the chondroprotective metalloproteinase ADAM15 is reduced in aging cartilage

Abstract: Objective The adamalysin metalloproteinase 15 (ADAM15) has been shown to protect against development of osteoarthritis in mice. Here, we have investigated factors that control ADAM15 levels in cartilage. Design Secretomes from wild-type and Adam15 −/− chondrocytes were compared by label-free quantitative mass spectrometry. mRNA was isolated from murine knee joints, either with or without surgical induction of osteoarthritis on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Studies have confirmed that IL-3, 42 M-CSF, 43 IL-4, 44 and IL-25 45 are involved in chondroprotection and chondrogenesis. Moreover, IL-13, 45 , 46 IL-10, 47 and IL-19 48 have been demonstrated to slow OA progression. IL-12 49 and IL-27 50 also exert anti-inflammatory effects.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have confirmed that IL-3, 42 M-CSF, 43 IL-4, 44 and IL-25 45 are involved in chondroprotection and chondrogenesis. Moreover, IL-13, 45 , 46 IL-10, 47 and IL-19 48 have been demonstrated to slow OA progression. IL-12 49 and IL-27 50 also exert anti-inflammatory effects.…”
Section: Resultsmentioning
confidence: 99%
“…2G and Table S7G). These pathways may underlie the many effects of cellular processes essential to homeostasis, including the cell cycle, cell survival, in ammation, metabolism, and apoptosis in OA progression [34][35][36][37][38][39], where interleukin-4 and interleukin-13 signaling pathways have been shown to underlie cartilage repair during OA progression through anti-in ammatory and chondroprotective mechanism [40][41][42]. The content of ShFCPC, in addition to a possible delivery mechanism through ECM molecules, provides us with an information database for the development of targeted therapeutics for speci c arthritis diseases such as OA.…”
Section: Discussionmentioning
confidence: 99%
“…ADAM15 belongs to the ADAM family of sheddases, a class of proteinases that are involved in the ectodomain shedding of transmembrane proteins and play a role in a number of biological processes including cell communication [25]. Both in vitro and in vivo studies have indicated a function for ADAM15 in a number of biological processes, including regulation of cartilage homeostasis.…”
Section: Discussionmentioning
confidence: 99%